Comparison of Some Heavy Metal Levels in the Muscle Tissue of Capoeta trutta Captured from Örencik Region of Keban Dam Lake (Elazığ) - Canpolat, Ozgür; Calta, Metin (My University, 2021)
Keban Dam Lake is the second largest dam lake in Turkey. In addition, it has the feature of being one of the most important dam lakes in our country in terms of both aquaculture potential and electricity generation. In this study, fish samples belong to Capoeta trutta caught from Örencik region of Keban Dam Lake were used. The concentrations of some heavy metals (copper, iron, zinc, chromium, nickel, cadmium, arsenic and mercury) in muscle of Capoeta trutta and the potential health risk from consumption of this fish species were examined. In addidion, the relationship between the heavy metal levels and some biological aspects of fish (weight, length and sex) were determined. As a result of the study, it was determined that the most and the least accumulated heavy metals in the muscle tissue of Capoeta trutta were zinc and cadmium respectively. The concentration of heavy metals showed differences according to weight, length and sex of fish. The results were found indicated that heavy metal levels in the muscle tissue of Capoeta trutta are below the tolerable values recommended by EPA, WHO and FAO. Therefore, there is not any risk for human consumption of this fish species.
Keywords: Biyoloji; Balıkçılık; Su Kaynakları; Deniz ve Tatlı Su Biyolojisi